PERKEMBANGAN SURATKHABAR DAN MAJALAH DI JOHOR SEBELUM PERANG DUNIA KEDUA: DEVELOPMENT OF THE PRESS IN JOHOR BEFORE THE SECOND WORLD WAR - Mahfood, Siti Zahrah; Musa, Mahani (SEJARAH: Journal of the Department of History, 2021)
Johor is often remembered as the state that witnessed the formation of the first Malay political party in this country, UMNO. Of similar significance, something that is often marginalised in Malaysian historiography, is the existence of myriad newspapers and magazines including the first women magazine in Malaya namely Bulan Melayu which was established in 1930. This article aims to examine the history of the emergence of newspapers and magazines in this state and their development before the Second World War. Some of the aspects looked into are the major locations in the publication of newspapers and magazines, the pioneers and factors contributing to its development. The study is using qualitative method and sources used in this research are newspapers and magazines that were published in Johor from the 1920s until 1941, besides official documents and records issued by the British and the Johor government. The findings of the research shows Johor’s involvement in newspapers and magazines before the Second World War was closely related to inspiration from the masses and the state in facing the pressure of British imperialism and as impact of modernisation undertaken by the state since the mid-19 century that witnessed development in the intellectual aspect that involved school teachers, religious schools, administrators and associations in the state. Received: 20 April 2021 Reviewed: 1 May 2021 Accepted: 28 June 2021